1868 Pa. Laws 321, No. 288, § 2, pt. 6. - (:unkn) unknown (My University, 1868)
To regulate, by ordinances . . . the storage, sale of gun powder, fire works and other inflammable or dangerous articles, and the location of refineries.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER